Impact of aerobic acclimation on the nitrification performance and microbial community of landfill leachate sludge. (1st March 2018) - Hira, Daisuke; Aiko, Nobuyuki; Yabuki, Yoshinori; Fujii, Takao
Abstract: Nitrogenous pollution of water is regarded as a global environmental problem, and nitrogen removal has become an important issue in wastewater treatment processes. Landfill leachate is a typical large source of nitrogenous wastewater. Although the characteristics of leachate vary according to the age of the landfill, leachates of mature landfill have high concentrations of nitrogenous compounds. Most nitrogen in these leachates is in the form of ammonium nitrogen. In this study, we investigated the bacterial community of sludge from a landfill leachate lagoon by pyrosequencing of the bacterial 16S rRNA gene. The sludge was acclimated in a laboratory-scale reactor with aeration using a mechanical stirrer to promote nitrification. On 149 days, nitrification was achieved and then the bacterial community was also analyzed. The bacterial community was also analyzed after nitrification was achieved. Pyrosequencing analyses revealed that the abundances of ammonia-oxidizing and nitrite-oxidizing bacteria were increased by acclimation and their total proportions increased to >15% of total biomass. Changes in the sulfate-reducing and sulfur-oxidizing bacteria were also observed during the acclimation process. The aerobic acclimation process enriched a nitrifying microbial community from the landfill leachate sludge. These results suggested that the aerobic acclimation is a processing method for the nitrification ammonium oxidizing throw the enrichment of nitrifiers. Improvement of this acclimation method would allow nitrogen removal from leachate by nitrification and sulfur denitrification. Highlights: Microbial community of sludge from a landfill leachate lagoon was investigated. The sludge was acclimated in a reactor with aeration to promote nitrification. The bacterial community was also analyzed after nitrification was achieved. Pyrosequencing analyses revealed the increase of nitrifying bacteria by acclimation. Changes in the sulfate-reducing and sulfur-oxidizing bacteria were also observed.